Dynamics of Recent Thymic Emigrants in Young Adult Mice - van Hoeven, Vera; Drylewicz, Julia; Westera, Liset; den Braber, Ineke; Mugwagwa, Tendai; Tesselaar, Kiki; Borghans, José A. M.; de Boer, Rob J. (Frontiers in Immunology, 2017)
The peripheral naive T-cell pool is generally thought to consist of a subpopulation of recent thymic emigrants (RTE) and a subpopulation of mature naive (MN) T cells with different dynamics. Thymus transplantation and adoptive transfer studies in mice have provided contradicting results, with some studies suggesting that RTE are relatively short-lived cells, while another study suggested that RTE have a survival advantage. We here estimate the death rates of RTE and MN T cells by performing both thymus transplantations and deuterium labeling experiments in mice of at least 12 weeks old, an age at which the size of the T-cell pool has stabilized. For CD4+ T cells, we found the total loss rate from the RTE compartment (by death and maturation) to be 4-fold faster than that of MN T cells. We estimate the death rate of CD4+ RTE to be 0.046 per day, which is 3-fold faster than the total loss rate from the MN T-cell compartment. For CD8+ T cells, we found no evidence for kinetic differences between RTE and MN T cells. Thus, our data support the notion that in young adult mice, CD4+ RTE are relatively short-lived cells within the naive CD4+ T-cell pool.